Allostatic load index in patients with pituitary tumours: a case control study - Strzelec, Martyna; Szcześniak, Dorota; Zendran-Zahorska, Iga; Kuliczkowska-Płaksej, Justyna; Słoka, Natalia; Kujawa, Krzysztof; Bolanowski, Marek; Jawiarczyk-Przybyłowska, Aleksandra (Frontiers in Endocrinology, 2025)
IntroductionProlonged exposure to pathogenic stress factors leads to multisystemic consumption of the body and adverse changes resulting in the development of allostatic load (AL). Stress plays a crucial role in the pathophysiology of many diseases, including endocrinopathies. The purpose of our study was to evaluate the allostatic load index in patients with pituitary tumours and compare it to a control group.Materials and methodsThe study group included 58 patients with hormonally active pituitary tumours and 52 patients without pituitary dysfunction, representing the control group. The AL index (ALI) was calculated based on 16 parameters grouped into the following categories: anthropometric parameters, cardiovascular markers, lipid and carbohydrate metabolism parameters, and inflammatory and hormonal markers.ResultsIn the group of patients with pituitary tumours, a statistically significantly higher AL index was noticed, regardless of the endocrine function of the adenoma, compared to the control group [7.00 (5.00–9.00) vs. 3.50 (2.00–5.00), p < 0.001]. Age significantly affected the AL index, while no such relationship was observed for education. Analysing specific AL biomarkers, patients with pituitary tumours had significantly higher Body Mass Index (BMI), systolic blood pressure and diastolic blood pressure. Individuals in the study group showed significantly higher levels of insulin, triglycerides and interleukin 6, and significantly lower levels of high-density lipoprotein cholesterol, dehydroepiandrosterone sulphate and albumin, compared to the control group.ConclusionsThe results of our study indicate the usefulness of the AL index as an integrated tool for assessing the cumulative impact of stress factors in pituitary diseases. In addition, patients with hormonally active pituitary tumours presented a higher cardio-metabolic risk. It is necessary to analyse the clinimetric data affecting AL, which is the next step of our study.